Queering code/space: the co-production of socio-sexual codes and digital technologies. Issue 11 (2nd November 2017) - Cockayne, Daniel G.; Richardson, Lizzie
Abstract: The mutual production of space by sexuality and technology has been differently addressed in the often-disparate disciplinary pursuits of queer geographies and critical studies of technology in geography. Building on Dodge and Kitchin's 'code/space, ' we highlight how studies of technology in geography are already concerned with questions of sexuality through the examination of biopolitics and the regulation of bodies, together with the (re-)establishment of new and old lines between the public and the private. The immanence of sexuality in code/space foregrounds the importance of spatial processes characterised by their difference and normativity in the geographies of technology. Queer geographies critically examine such different experiences and processes of differentiation through space in their nuanced conceptualisations of spatial regulation and transgression. We illustrate how these two bodies of geographical scholarship might be synthesised by outlining three approaches for studies of 'queer code/space.' To show how there are a variety of relationships between sexuality, code, and space, we play on the double entendre of 'code' as a set of social rules and norms, and 'code' as the set of algorithmic instructions underlying software systems. In both senses, codes constrain forms of intimate life, but can also transgress, disrupt, and distribute the norm. To queer code/space is to emphasise the complexities of difference and normativity in living with technologies, where technologies might both proliferate and regulate socio-spatial experience.